Beer but not wine, hard liquors, or pure ethanol stimulates amylase secretion of rat pancreatic acinar cells in vitro - Gerloff, Andreas; Singer, Manfred V.; Feick, Peter (Alcoholism, 2009)
Background: In contrast to pure ethanol, the effect of alcoholic beverages on the exocrine pancreas is greatly unknown. Besides ethanol, alcoholic beverages contain numerous nonalcoholic constituents which might have pathophysiological effects on the pancreas. The aim of the present study was to investigate whether some commonly used alcoholic beverages and pure ethanol influence the main function of rat pancreatic acinar cells, i.e., enzyme output in vitro. Methods: Rat pancreatic AR4-2J cells were differentiated by dexamethasone treatment for 72 hours and freshly isolated pancreatic acini were prepared from Sprague-Dawley rats using collagenase digestion. After incubation of cells in the absence or presence of 1 to 10% (v/v) beer (containing 4.7% v/v ethanol), 10% (v/v) wine (containing 10.5 to 12.5% v/v ethanol), 10% (v/v) hard liquor (such as whisky, rum, and gin), or of the corresponding ethanol concentrations (4.03 to 80.6 mM) for 60 minutes, protein secretion was measured using amylase activity assay. Results: Incubation of AR4-2J cells with beer caused a dose-dependent stimulation of basal amylase secretion that was significant at doses of beer above 0.5% (v/v). Stimulation with 10% (v/v) beer induced 92.7 ± 25.2% of maximal amylase release in response to the most effective cholecystokinin (CCK) concentration (100 nM). In contrast, ethanol (up to 80.6 mM) did neither stimulate nor inhibit basal amylase release. Lactate dehydrogenase measurement after treatment of AR4-2J cells with beer for 24 hours indicated that the increase of amylase release was not due to cell membrane damage. Wine and hard liquor had no effect on basal amylase secretion neither diluted to the ethanol concentration of beer nor undiluted. In freshly isolated rat pancreatic acinar cells beer dose-dependently stimulated amylase secretion in a similar manner as in AR4-2J cells. Conclusions: Our data demonstrate that beer dose-dependently increases amylase output. Since neither ethanol nor the other alcoholic beverages tested caused stimulation of amylase release, our findings indicate that nonalcoholic constituents specific for beer are responsible for this increase. These as yet unknown compounds have to be identified and considered in further studies of ethanol-induced pathological and functional changes of the pancreas.